Hatvani István, a polihisztor professzor - Gaál, Botond (Gerundium, 2019)
István Hatvani, the polyhistor Professor. István Hatvani interpreted his professorship as profession devoted to cultivation and instruction of sciences. Besides being a determined theologian of the Reformed Church, he also owned profund knowledge in all disciplines of natural sciences of his age. As well, he was aware of the relationship between these two fields of sciences and philosophy. According to his considerations, the Newtonian view of nature was acceptable, which explains him discarding the ‚logic-deductive based science concept’ of Christian Wolff. His passion to work, as well as to his marriage was deeply influenced by his Christian faith.